PENGARUH PENGGUNAAN MEDIA GRAFIS GAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS AL- WASHLIYAH SORKAM - Mita Wulandari; Hamdi Abdul Karim (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The purpose of this study was to determine the effect of using graphic image media on student learning outcomes at MTs Al-Washliyah Sorkam. This study is a quantitative study with a research design that uses Quasi Experiment. The sample of this study was grade VII students at MTs Al-Washliyah Sorkam with a sample size of 60 students. The sample of the study was class VII A Experiment using graphic image media and class VII B Control with conventional methods, data analysis techniques using hypothesis testing with paired sample tests. The results showed that there was a significant effect on the use of graphic image media on student learning outcomes in the subject of aqidah akhlak at MTs Al-Washliyah Sorkam class VII A. As these results prove that the value of the experimental class Sig (2-tailed) = 0.000 while alpha (0.000 <0.05), with an average value using graphic image media of 72.83.